Curriculum Construction of Traditional Islamic Boarding Schools in Padang Lawas Regency, North Sumatra Province - fahmi Anwar Nasution; Mas'ud Zein; Alpizar Alpizar (Postgraduate, University of Mataram, 2026)
This study examines the curriculum of traditional Islamic boarding schools (pesantren) in Padang Lawas Regency, North Sumatra, Indonesia, within the context of ongoing efforts to balance classical Islamic educational traditions with contemporary educational demands. The objectives of this research are to analyze: (1) the current condition of the traditional pesantren curriculum, (2) the obstacles encountered in its implementation, and (3) the construction of the curriculum within learning practices. This research employed a qualitative field research approach conducted directly in traditional pesantren across Padang Lawas Regency. The study involved 18 traditional Islamic boarding schools as the research population. Data were collected through observations and in-depth interviews with key stakeholders and were analyzed using qualitative data analysis techniques to generate a comprehensive understanding of curriculum implementation and development. The findings indicate that the traditional pesantren curriculum primarily consists of learning materials, classical Islamic texts (kitab kuning), instructional methods, and evaluation systems. The curriculum is predominantly oriented toward Islamic sciences, reflecting the historical and religious identity of traditional pesantren. However, several challenges were identified, including unsystematic curriculum planning, limited diversity in teaching methods, inadequate human resource competencies, insufficient educational facilities and infrastructure, non-standardized evaluation mechanisms, low adaptability to contemporary educational developments, and management systems that remain largely traditional. The study further reveals that curriculum construction in these pesantren has gradually evolved through the integration of classical Islamic studies with general education, science and technology, and vocational competencies such as entrepreneurship. Despite these developments, Islamic studies continue to serve as the central component of the curriculum. This integration reflects an effort to maintain the authenticity of traditional Islamic education while responding to the needs of modern society. In conclusion, the traditional pesantren curriculum in Padang Lawas Regency is characterized by strong classical Islamic foundations and a commitment to preserving religious values. Nevertheless, systematic curriculum reform, improved institutional management, enhanced teaching competencies, and greater integration of contemporary knowledge are necessary to strengthen its relevance, effectiveness, and sustainability in the modern educational era.